Severe retinal degeneration in women with a c.2543del mutation in ORF15 of the RPGR gene - Kousal, Bohdan; Skalicka, Pavlina; Valesova, Lucie; Fletcher, Tracy; Hart-Holden, Niki; O'Grady, Anna; Chakarova, Christina F; Michaelides, Michel; Hardcastle, Alison J; Liskova, Petra (Molecular vision, 2014)
PURPOSE: To describe the genotype-phenotype correlation and serial observations in a five-generation Czech family with X-linked retinitis pigmentosa (XLRP) associated with severe visual impairment in women. METHODS: Comprehensive ophthalmological examination including spectral domain optical coherence tomography (SD-OCT) was performed. Based on the pedigree structure and women being severely affected, autosomal dominant inheritance was suspected, and screening for known mutations by genotyping microarray was performed. Subsequently, direct sequencing of ORF15 RPGR was undertaken. RESULTS: Eighteen family members (nine women and nine men) were examined. A pathogenic variant, c.2543del in ORF15 of RPGR, was found to segregate with disease. The oldest woman and her two sisters had no perception of light in their sixth decade. Four women and five men had signs and symptoms of typical XLRP, including moderate to high myopia. Three other women also had moderate to high myopia and myopic astigmatism but without the presence of bone spicule-like formation. Severe disruption of macular architecture on SD-OCT was equally common in both sexes. Only one 32-year-old female carrier had clinically normal findings. Subfoveal choroidal thickness was decreased in all affected men and in all female carriers, except the only carrier with a normal fundus examination. CONCLUSIONS: The c.2543del mutation in ORF15 of RPGR is associated with a severe phenotype in the women in this family. The presence of a significant myopic refractive error, in the absence of male-to-male transmission, may be indicative of X-linked inheritance. Measurements of choroidal thickness may help in clinically identifying carrier status.
Keywords: Heterozygote; Humans; Child; Adolescent; Retinitis Pigmentosa; Sex Factors; lidé; choroidea; Eye Proteins; otevřené čtecí rámce; Open Reading Frames; geny vázané na chromozom X; molekulární sekvence - údaje; retinopathia pigmentosa; Pedigree; Choroid; dítě; Base Sequence; rodokmen; Female; Severity of Illness Index; optická koherentní tomografie; lidé středního věku; Genes, X-Linked; Male; Tomography, Optical Coherence; mladiství; sekvence nukleotidů; heterozygot; Adult; stupeň závažnosti nemoci; dospělí; Genes, Dominant; sexuální faktory; Molecular Sequence Data; Sequence Deletion; senioři; Aged; retina; sekvenční delece; Middle Aged; ženské pohlaví; mužské pohlaví; dominantní geny; Retina; oční proteiny